The degree of fluid absorption during hysteroscopic surgery in patients pretreated with goserelin - Taskin, O; Yalcinoglu, A; Kucuk, S; Burak, F; Ozekici, U; Wheeler, JM (Journal Amer Assoc Gynecologic Laparoscopists, 1996)
Study Objective. To assess the effects of pretreatment with the gonadotropin-releasing hormone analog goserelin on fluid absorption in patients undergoing hysteroscopic endometrial ablation. Design. Prospective, randomized, placebo-controlled study. Setting. A university-based clinic. Patients. Thirteen women with dysfunctional uterine bleeding who were scheduled for electrosurgical hysteroscopic ablation. interventions. Seven women were randomized to receive luteal phase goserelin 3.75 mg and six saline in the menstrual cycle approximately 10 weeks before surgery. Operative hysteroscopy was carried out with glycine 1.5% mixed with 2% alcohol medium under constant pressure as an irrigant. The amount of irrigant used, irrigant deficit, blood levels of albumin and ethanol, hematocrit, hemoglobin, changes in sodium levels, and central venous pressure were compared between the groups. Measurements and Main Results. All of the patients had an unsuccessful course of medical therapy for at least 3 months and a normal endometrial biopsy. The age, weight, and uterine size were similar between the groups. The mean volume of irrigant used and operating time were similar in both groups (4.18 +/- 0.2 vs 4.5 +/- 0.5 L, and 33.7 +/- 1.5 vs 37 +/- 2.1 min). Although operating time, volume deficit, decrease in protein level, and hematocrit were less in the goserelin than in the saline group, the differences were not statistically significant (p >0.05). The ethanol levels in blood, decrease in Na+, and irrigant deficit were significantly lower in the goserelin than in the saline group (17.4 +/- 3.8 vs 25.3 +/- 4.2 mg/ml, 6.7 +/- 1.2 vs 9.1 +/- 0.9 mEq/L, and 0.49 +/- 0.08 vs 0.66 +/- 0.05 L, respectively; p <0.05). Conclusion. Based on these results we conclude that in women undergoing hysteroscopic endometrial ablation, pretreatment with goserelin may decrease the absorption of hysteroscopic medium, prevent fluid overload, and improve the outcome possibly by causing hypovascularity and decreased endometrial growth.
American-Association-of-Gynecologic-Laparoscopists 24th Annual Meeting -- NOV 08-12, 1995 -- ORLANDO, FL
Keywords: Endometrial Ablation; Resection; Hyponatremia; Women